Implementasi Internet Of Things Dalam Transformasi Digital Kesehatan (Literature Review) - Seftia Angelina; Saut Dohot Siregar (PT. Hasba Edukasi Mandiri, 2025)
The Internet of Things (IoT) has emerged as one of the key innovations in modern healthcare. By connecting medical devices, IoT provides real-time access to patient data, enhances service efficiency, and supports faster clinical decision-making. This literature review evaluates the application of IoT in healthcare, covering its benefits in remote monitoring, the development of smart devices, and the challenges faced regarding data security and infrastructure. This study employs a qualitative descriptive approach with quality assessment parameters to evaluate relevant literature. The findings reveal that IoT plays a significant role in creating more accessible healthcare services, although further development is needed to address existing technological limitations.